Designing Sustainability for All The Design of Sustainable Product-Service Systems Applied to Distributed Economies - Vezzoli, Carlo; Garcia Parra, Brenda; Kohtala, Cindy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book introduces design for Sustainable Product-Service Systems (S.PSS) and for Sustainable Distributed Economies (S.DE). These are introduced as technical and operative tools for the development of a new generation of designers, responsible and capable of designing environmentally-sustainable products. The book provides a comprehensive theoretical framework but also a practical tool to support the design process. It overviews methodologies, tools and strategies for Sustainable PSS design applied to Distributed Economies (DE) and provides strategies and design guidelines. All of these are highlighted and expanded upon with international case studies.
Design for Sustainability -- Distributed Economies (DE) and locally-based Sustainability -- S.PSS applied to DE: a win-win model for Sustainability -- New competences in Design (the knowledge-base) -- Designing Sustainability for All (the know-how) -- Methods and Tools for SD4SA -- Practical Examples of SD4SA Approach.
Keywords: Engineering design; Management; Economic development; Industrial engineering; Production engineering; Engineering Design; Management; Development Studies; Industrial and Production Engineering